Infrastructure Management for Improved Learning Outcomes: Insights from Junior High Schools in Southwest Aceh, Indonesia - Istakri, Dedi; Sofyan, Hizir; Ismail, Ismail (Heca Sentra Analitika, 2024)
This qualitative study explores the management of facilities and infrastructure at two junior high schools in Southwest Aceh Regency, Indonesia (SMP Negeri 1 Susoh and SMP Negeri 2 Susoh) and examines its impact on learning quality. The research methodology includes observations, structured interviews, and documentation to collect data from key stakeholders such as principals, deputy principals, and teachers. The findings emphasize the critical role of detailed planning and collaboration among teachers, principals, and school development teams in aligning facility needs with curriculum requirements. Efficient use, storage, maintenance, and care of educational assets are essential for maximizing their functionality and longevity. The study also highlights the importance of comprehensive inventory management that adheres to regulatory guidelines to ensure effective resource control and supervision. However, the schools face challenges including limited land availability, insufficient funding, human resource constraints, and inadequate government support, which impede their ability to provide well-rounded learning environments. The study points out the necessity for ongoing improvement efforts by principals to adapt educational facilities to evolving educational demands. It recommends prioritizing investments in facilities, staff training, and policy enhancements to address these challenges and foster comprehensive educational development. Future research should assess the effectiveness of these management practices in various contexts and their long-term impact on student outcomes.